2017
DOI: 10.1038/s41430-017-0040-7
|View full text |Cite
|
Sign up to set email alerts
|

Standardized feeding and probiotic supplementation for reducing necrotizing enterocolitis in preterm infants in a resource limited set up

Abstract: Introduction of SFR and RPS was associated with significant reduction in NEC ≥ Stage II and the composite outcome of NEC ≥ Stage II /mortality in preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In more than 90% of cases, NEC develops in premature infants (ie, those born before 37 weeks' gestational age), indicating that NEC is fairly specific to the underdeveloped gastrointestinal tract. 2 , 28 Intestinal bacteria are linked to the development of NEC because NEC occurs after colonization of the intestine has occurred, although NEC is treated with broad-spectrum antibiotics that target enteric microbes, 29 , 30 , 31 suggesting that bacterial–host signaling plays a role in NEC development. Specific clinical risk factors for NEC include the administration of acid-suppressive H2 blockers, 32 , 33 , 34 excessive antibiotic use, 35 brief episodes of hypoxia, 36 the presence of chorio-amnionitis (an infection of the lining of the uterine cavity during gestation), 37 and the administration of formula feeds.…”
Section: Clinical Risk Factors For Necmentioning
confidence: 99%
“…In more than 90% of cases, NEC develops in premature infants (ie, those born before 37 weeks' gestational age), indicating that NEC is fairly specific to the underdeveloped gastrointestinal tract. 2 , 28 Intestinal bacteria are linked to the development of NEC because NEC occurs after colonization of the intestine has occurred, although NEC is treated with broad-spectrum antibiotics that target enteric microbes, 29 , 30 , 31 suggesting that bacterial–host signaling plays a role in NEC development. Specific clinical risk factors for NEC include the administration of acid-suppressive H2 blockers, 32 , 33 , 34 excessive antibiotic use, 35 brief episodes of hypoxia, 36 the presence of chorio-amnionitis (an infection of the lining of the uterine cavity during gestation), 37 and the administration of formula feeds.…”
Section: Clinical Risk Factors For Necmentioning
confidence: 99%
“…Twenty studies were identified that described aspects of guideline implementation or health systems strengthening to improve outcomes of preterm babies in LMICs [ 59 , 63 , 104 , 128 , 130 , 135 , 142 , 144 , 145 , 157 , 177 , 178 , 180 , 181 , 188 , 191 , 197 - 200 ].…”
Section: Resultsmentioning
confidence: 99%
“…TFF and duration of hospital stay was reported in 15 (27-30, 32-34, 41, 44, 46, 48, 50, 51, 53) and 10 studies (26,27,29,30,33,41,48,51,53,55), respectively. The corresponding total sample sizes for these outcomes were 14,215 (Probiotic: 5580, Control: 8635) and 10,289 (Probiotic: 3694, Control: 6595), respectively.…”
Section: Secondary Outcomesmentioning
confidence: 99%